Association study of candidate genes with obesity and metabolic traits in antipsychotic-treated patients with first-episode psychosis over a 2-year period. (May 2020) - Gassó, Patricia; Arnaiz, Joan Albert; Mas, Sergi; Lafuente, Amalia; Bioque, Miquel; Cuesta, Manuel J; Díaz-Caneja, Covadonga M; García, Clemente; Lobo, Antonio; González-Pinto, Ana; Parellada, Mara; Corripio, Iluminada; et al.
Aims: Patients with a first episode of psychosis (FEP) often display different metabolic disturbances even independently of drug therapy. However, antipsychotic (AP) treatment, especially with second-generation APs, is strongly linked to weight gain, which increases patients' risk of developing obesity and other metabolic diseases. There is an important genetic risk component that can contribute to the appearance of these disturbances. The aim of the present study was to evaluate the effect of polymorphisms in selected candidate genes on obesity and other anthropometric and metabolic traits in 320 AP-treated FEP patients over the course of a 2-year follow-up. Methods: These patients were recruited in the multicentre PEPs study (Phenotype−genotype and environmental interaction; Application of a predictive model in first psychotic episodes). A total of 127 validated single nucleotide polymorphisms (SNPs) in 18 candidate genes were included in the genetic analysis. Results: After Bonferroni correction, SNPs in ADRA2A, FTO, CNR1, DRD2, DRD3, LEPR and BDNF were associated with obesity, abdominal circumference, triglycerides, HDL cholesterol, and/or percentage of glycated haemoglobin. Conclusions: Although our results should be interpreted as exploratory, they support previous evidence of the impact of these candidate genes on obesity and metabolic status. Further research is required to gain a better knowledge of the genetic variants that can be considered relevant metabolic risk factors. The ability to identify FEP patients at higher risk for these metabolic disturbances would enable clinicians to better select and control their AP treatment.